Planeamiento estratégico para Hatun Wasi SRL - Medrano Cocha, Liana Mariela (2023)
We present the strategic plan for Hatun Wasi SRL, a two-star hotel located in the city of Huaraz, province and region of Ancash, an area with high tourism potential in the process of development and post-pandemic recovery. The purpose of this plan is to propose lines of action to the owners that contribute to achieving the company's objectives. Five chapters have been developed, which cover the analysis of the internal and external environment, as well as the competitive profile, for the formulation, implementation and control of the strategies to be implemented. In addition, Haxtun Wasi seeks to consolidate its proposal under the cost leadership strategy, with the value proposition being to provide a personalized service with familiar treatment and quality culture with customers. In order to meet its objectives, Hatun Wasi must make strategic alliances with distribution channels and implement the format of temporary rentals, so it must align the objectives with the functional plans of each area of the organization.